Association between thyroid function and osteopenia or osteoporosis: a cross-sectional study in China - Ling Zhang; Chao Ma; Xin Yin; Fenglian Zhang; Xiuyan Fang; Chen Zhang; Lei Shang; Li Ma (Scientific Reports)
Abstract Thyroid dysfunction is associated with bone health, but the relationship with osteopenia remains unclear. This study aimed to investigate the association between thyroid function and osteopenia/osteoporosis across different age groups. The study included 4508 men and 1438 women who underwent health check-ups between January 2021 and December 2023. Bone mineral density (BMD) was measured using dual energy X-ray absorptiometry. Logistic regression analysis was employed to evaluate the association between thyroid function and the risk of osteopenia/osteoporosis. The results showed that in postmenopausal women, both hyperthyroidism and age increased the risk of osteopenia and osteoporosis, while body mass index (BMI) was negatively correlated with both conditions. In men over 50, hyperthyroidism and age were also linked to a higher risk of osteoporosis. Among postmenopausal women, higher thyroid-stimulating hormone (TSH) levels were negatively associated with osteopenia risk. In men aged 50 and above, free thyroxine (fT4) levels were inversely related to osteopenia and osteoporosis risk. In men under 50, fT4 levels were negatively linked to the risk of low bone mass. These findings suggest that TSH and fT4 levels may influence bone health, with these effects varying by age and sex. Further studies are needed to confirm these findings and explore potential mechanisms.